You have to be twice as good and work twice as hard: a mixed-methods study of perceptions of sexual harassment, assault and women's leadership among female faculty at a research university in the USA. (2019) - Evans, Dabney P.; Sales, Jessica M.; Krause, Kathleen H.; del Rio, Carlos
Abstract: Introduction: The purpose of this study was to examine the perceptions of institutional policies and practices for the prevention of and response to gender inequities as experienced by female faculty working in the health sciences at a US research university. Methods: Data from the institution's Faculty Campus Climate Survey ( n = 260 female faculty) were coupled with qualitative interviews ( n = 14) of females in leadership positions, exploring campus climate, and institutional policies and practices aimed at advancing women. Results: Two-thirds (59%) of the female faculty respondents indicated witnessing sexual harassment and 28% reported experiencing sexual harassment. Several organizational themes emerged to address this problem: culture, including cultural change, transparency, and accountability. Conclusions: The findings reveal the ways in which university culture mimics the larger societal context. At the same time, the distinct culture of higher education processes for recruitment, career advancement – specifically tenure and promotion – are identified as important factors that require modifications in support of reductions in gender inequalities.